Phenomenological Study: Experience of Voluntary Nurses in Providing Health Services During The COVID-19 Pandemic - Hotma Royani Siregar; Febrina Angraini Simamora (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2021)
Introduction: The COVID-19 pandemic has certainly caused a significant crisis in various groups and populations in the world, especially nurses. The roles and responsibilities that nurses have to play become a dilemma when they not only have to protect themselves, but also their colleagues and their families from this deadly virus infection. This study was to identify the experiences of nurses in providing nursing care to patients during COVID-19 pandemic. Methods: The study used a phenomenological design. Ten participants were selected by purposive sampling. The data were gathered by conducting in-depth interviews and analyzed by Colllaizi’s method. The data were collected in hospitals of the South Tapanuli area. Results: The data were gathered by conducting in-depth interviews and analyzed by Collaizi’s method. The result emerged five themes, namely: 1) Motivation of voluntary nurses to provide health services in the COVID-19 pandemic; 2) voluntary nurse psychological response; 3) problems faced by voluntary nurses; 4) the benefits of being a voluntary nurse during the COVID-19 pandemic; 5) the expectations of voluntary nurses. Conclusion: Voluntary nurses continue to carry out their duties in providing health services in the Covid-19 pandemic even though without any compensation received. The result of this research is recommended to the hospital and government giving the needs of voluntary nurses while providing health services during COVID-19 pandemic.